Design of System Monitoring for Floating Solar Pane Energy Based on IoT: Blynk - Suprayogi, Febri; Al Fatah, Sachmalevi; Wulandari, Rindi (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2024)
Floating Solar Power Plant is one of the energy plants that does not damage nature because solar panels are new renewable energy or EBT and are very effective in supporting world conservation and can be applied in remote areas in Indonesia. This research aims to design and create an IoT-based Floating Solar Power Plant monitoring system. The research methodology used is the experimental method by designing hardware and software monitoring systems, the hardware consists of temperature sensors, voltage sensors, and current sensors connected to a microcontroller. The result of this research is a monitoring system on floating solar panels using esp8266, DHT11, and ACS712. Tests conducted on the monitoring system have an average error value of 1.08% for temperature measurements, these results are based on comparing data on the system and manual measurements with calibrated measuring instruments. Current and voltage measurements have an error value of 4.65% and 2.20%.  Based on the test results, it can be said that the monitoring system can work well, because the error value obtained is relatively small in the measurement of temperature, current, and voltage compared to the manual monitoring, from a fairly small error value can be concluded that the monitoring of the floating solar power plant made has worked well.